A brain microdialysis study on 5-HT release in freely moving rat lines selectively bred for differential 5-HT1A receptor function - Gonzalez,L.E. (2003)
Breeding for high and low hypothermic responses to systemic administration of a serotonin1A (5-HT1A) receptor agonist (8-hydroxy-2-(di-n-propylamino)tetralin, 8-OH-DPAT) has resulted in high DPAT-sensitive (HDS) and low DPAT-sensitive (LDS) lines of rats, respectively. These lines also differ in several behavioral measures associated with stress. In the present microdialysis study we observed that basal 5-HT concentrations in the prefrontal cortex and dorsal hippocampus did not differ significantly between HDS and LDS rats. Thus, behavioral differences between the HDS and LDS lines might not be attributed to differences in basal 5-HT release. However, both lines had lower basal levels of 5-HT release than their randomly bred control group (random DPAT-sensitive, RDS) in the prefrontal cortex (mean ± SEM, pg/20 µl, was 3.0 ± 0.4 for LDS, 3.8 ± 0.3 for HDS and 6.4 ± 0.6 for RDS; F(2,59) = 5.8, P<0.005). The administration of (±)-fenfluramine (10 mg/kg) induced a greater increase in hippocampal 5-HT levels in HDS rats (500%) as compared with LDS (248%) or RDS (243%) rats (P<0.0001). There were no significant differences in the prefrontal cortex among lines, with a fenfluramine-induced 5-HT increase of about 900% in the three groups. This differential response to fenfluramine may be due to functional alterations of hippocampal 5-HT reuptake sites in the HDS line.